(untitled) (Bangladesh Journal of Infectious Diseases, 2018)
Background: Elucidating differences in HLA DRB1* genes distribution may be useful in understanding the molecular pathogenesis of viral hepatitis B. Objective: The aim of the study was to find out the HLA DRB1*15 gene susceptibility among acute and chronic Hepatitis B infected Bangladeshi patients. Methodology: This cross-sectional study was carried out in the Department of Virology at Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh during the period of June 2012 to June 2013 for a period of one year. Evaluation HLA DRB15*gene distribution was performed among acute hepatitis B and chronic hepatitis B infected (HBV) Bangladeshi patients. HLA DRB15*gene distribution was detected by conventional PCR followed by agarose gel electrophoresis. Result: A total of 60 serologically pre-diagnosed 30 acute hepatitis B and 30 chronic hepatitis B infected (HBV) Bangladeshi patients were evaluated. The study revealed a significant increase of DRB1*15 allele among chronic hepatitis B infected patients compared to acute hepatitis B (46.7% vs 13.3%; RR=5.8, X2 test=7.2; P< 0.05). This is the first report to investigate HLA DRB1* gene associations among acute and chronic HBV infected Bangladeshi patients. Conclusion: In conclusion HLA DRB1*15 is more frequent in chronic hepatitis B infected Bangladeshi patients compared to acute hepatitis B. Bangladesh Journal of Infectious Diseases, June 2018;5(1):3-9